2017
DOI: 10.1111/jth.13748
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant factor XIII prophylaxis is safe and effective in young children with congenital factor XIII‐A deficiency: international phase 3b trial results

Abstract: Background Factor XIII deficiency is a rare, severe congenital bleeding disorder. Monthly prophylaxis with recombinant FXIII A-Subunit (rFXIII) has demonstrated favorable safety and efficacy in patients aged ≥ 6 years, and may similarly benefit younger children. Objective To evaluate the long-term safety and efficacy of rFXIII in children aged < 6 years with congenital FXIII A-subunit deficiency. Patients/methods Six children, who had previously completed a single-dose pharmacokinetic trial of rFXIII, received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…30 Despite that, a potential limitation was the low number of children/adolescents ( n = 16) participating in the mentor™2 trial; however, the current mentor™2 results support those from the mentor™5 trial, which showed efficacy and safety in six paediatric patients aged 1 to 4 years, in which rFXIII-A 2 prophylaxis was well tolerated and provided appropriate haemostatic coverage; the ABR was 0. 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Despite that, a potential limitation was the low number of children/adolescents ( n = 16) participating in the mentor™2 trial; however, the current mentor™2 results support those from the mentor™5 trial, which showed efficacy and safety in six paediatric patients aged 1 to 4 years, in which rFXIII-A 2 prophylaxis was well tolerated and provided appropriate haemostatic coverage; the ABR was 0. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 17 Similarly, the paediatric mentor™5 showed excellent efficacy and safety of prophylaxis with 35 IU/kg rFXIII-A 2 dosed every 4 weeks in patients aged <6 years. 18 Previous reports have shown similar pharmacokinetics (PK) in young children to that of older children and adults. 19 20 In the mentor™ programme to date, no patients treated with rFXIII-A 2 have developed FXIII-neutralizing antibodies (i.e., FXIII inhibitors).…”
Section: Introductionmentioning
confidence: 96%
“…Of these adverse events, 20 experienced a possible pathogen transmission, 12 a hypersensitivity reaction, 7 a possible thromboembolic event, and 5 developed a possible inhibitor [ 23 ]. For Tretten®, an international phase 3b trial exploring its safety and efficacy in pediatric patients with congenital factor XIII deficiency found that prophylaxis over 1.8–3.5 years dropped the annualized bleeding rate to zero with mostly mild adverse events [ 24 ]. Over the 16.6 patient years of the study, there were no thromboembolic events or hypersensitivity reactions observed [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…For Tretten®, an international phase 3b trial exploring its safety and efficacy in pediatric patients with congenital factor XIII deficiency found that prophylaxis over 1.8–3.5 years dropped the annualized bleeding rate to zero with mostly mild adverse events [ 24 ]. Over the 16.6 patient years of the study, there were no thromboembolic events or hypersensitivity reactions observed [ 24 ]. Of note, during the study, two patients experienced a head injury and neither developed an intracranial hemorrhage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a recent study reported on 6 children with factor XIII-A deficiency who had received once-monthly prophylaxis with recombinant factor XIII-A: the prophylaxis was well tolerated and no anti-FXIII antibodies were detected. Another study reported that prophylaxis was effective with an annualized bleeding rate of zero [23].…”
Section: Discussionmentioning
confidence: 99%